Dual‐band balanced‐to‐single‐ended crossover based on composite right‐ and left‐handed transmission lines. Issue 8 (1st April 2020) - Bayat, M.; Shahi, H.; Mazloum, J.
Abstract : This Letter presents a balanced‐to‐single‐ended (BS) crossover for dual‐band applications by using two rings included of composite right‐ and left‐handed (CRLH) transmission lines (TLs) with controllable frequency ratio feature. Two dumbbell defected ground structures (DGSs) are employed through balanced TLs to suppress out‐of‐band common‐mode. Theoretical analysis expresses that the frequency ratio can be controlled by suitable selecting of the element values and the number of designing cells of the CRLH TLs. Furthermore, desired impedances and electrical lengths of DGSs are obtained at the frequency of common‐mode rejection by using even‐ and odd‐mode analyses. To validate the proposed structure, a dual‐band BS crossover operating at 1.8 and 4.2 GHz is fabricated. Measurement results show that the fabricated proposed structure has good performance at the designed frequency bands.